Hey guys, I'm just stuck on the manipulation part of this problem but I'll set it up for ya'll.

Y=√(2x-x^2)

1/2≤x≤3/2

Rotating around the X-Axis

I set up the problem and plugged it into the equation which I believe is,

S=∫2πy√(1+(dy/dx))dx

When I plug in the derivative of Y, (1-x)/√(2x-x^2) under the square root in the main equation, I get lost as what to do next. I tried a few things but I'm either missing something or just flat out messing up my manipulation.

Thanks for your help! Audio